The effect of overspending on retirement preparation - Lynn, Christina (Kansas State University, 2023)
The current study addressed the research question of how overspending was related to retirement preparation. A commonsense answer to this question would be clear: overspending should negatively impact retirement preparation. However, the existing body of knowledge did not provide evidence to support or deny this assumption. The current study tested two different theoretical frameworks, the Behavioral Life Cycle Hypothesis and Life History Theory, to answer this research question and found both to provide valuable insight. Three data sets were used, including the Survey of Household Economic Decisionmaking (SHED), the Survey of Consumer Sciences (SCF), and the National Financial Capability Study (NFCS), to conduct logit and OLS regressions in testing the hypotheses. The main findings were (a) a short-term time preference, poor economic expectations, risky behavior, and retirement life expectancy were found to be strong positive predictors of overspending, and (b) partial support for overspending being negatively associated with retirement preparation. Because the overspending measurements were only negatively related to retirement preparation in a little over half the analyses, it pointed to a new cultural norm where one’s overspending behavior does not necessarily reflect one’s retirement preparation behavior. Implications of the current study included support for tightening credit card policy, exposing a lack of awareness on overspending as well as providing practical approaches for avoiding overspending behavior, and the value of using multiple data sets as a robustness check.
Keywords: Retirement preparation; Savings; Overspending; Self-control; Life history theory; Behavioral life cycle hypothesis